2022
DOI: 10.1186/s40104-022-00768-2
|View full text |Cite
|
Sign up to set email alerts
|

Poultry genetic heritage cryopreservation and reconstruction: advancement and future challenges

Abstract: Poultry genetics resources, including commercial selected lines, indigenous breeds, and experimental lines, are now being irreversibly lost at an alarming rate due to multiple reasons, which further threats the future livelihood and academic purpose. Collections of germplasm may reduce the risk of catastrophic loss of genetic diversity by guaranteeing that a pool of genetic variability is available to ensure the reintroduction and replenishment of the genetic stocks. The setting up of biobanks for poultry is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 155 publications
0
4
0
Order By: Relevance
“…Wood et al [6] reported that attempts to preserve in situ rare indigenous livestock breeds should be predictive, and so it is necessary to incorporate changes in environmental conditions into strategies related to the conservation of bioresources. Both intensification of production and propagation of new lines or breeds of livestock species with high genetic merit or high productivity can significantly destabilize the global diversity of domesticated animals [2,28,31,32]. Therefore, countries, including Poland, are developing adequate procedures aimed at the protection of livestock breeds.…”
Section: Biotechnological Assumptions Of Ex Situ Conservation In Live...mentioning
confidence: 99%
“…Wood et al [6] reported that attempts to preserve in situ rare indigenous livestock breeds should be predictive, and so it is necessary to incorporate changes in environmental conditions into strategies related to the conservation of bioresources. Both intensification of production and propagation of new lines or breeds of livestock species with high genetic merit or high productivity can significantly destabilize the global diversity of domesticated animals [2,28,31,32]. Therefore, countries, including Poland, are developing adequate procedures aimed at the protection of livestock breeds.…”
Section: Biotechnological Assumptions Of Ex Situ Conservation In Live...mentioning
confidence: 99%
“…Currently, several different germplasm preservation methods are used to preserve poultry gametes, including semen, PGCs (primordial germ cells), somatic cells, and gonads, which are used to preserve poultry gametes [11]. However, the effectiveness of semen freezing is not universally guaranteed due to factors such as breed, age, and preservation techniques [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, advanced and broad programs for the conservation of animal genetic resources are recommended to associate the priority in situ technique with the complementary ex situ in vitro technique in order to improve conservation potential and prevent the risk of dramatic or even total loss in biodiversity [16]. The implementation of the ex situ in vitro technique is considered essential to halt the current drain in biodiversity and rescue extant resources in the poultry sector, including commercial lines, indigenous breeds and experimental lines [17].…”
Section: Introductionmentioning
confidence: 99%